Grid-Connected Integrated Community Energy System. Final Report, August 9, 1977--March 22, 1978. Volume I, Phase II. [Clark University] (Clark University (Worcester, Mass.), 1978)
Clark University represents an attractive site for demonstration of cogeneration. The results of Phase I are briefly reviewed. This report provides an update on issues that were incompletely resolved in the Phase I report. Section 2 provides additional documentation on institutional issues involved in the proposed demonstration. Section 3 provides a preliminary design analysis that clearly defines the choice of engine and provides revised operating data in light of additional load profile studies. It is found that a Sulzer No. 6-oil-burning 1405-kW diesel with ebullient cooling and exhaust-gas heat recovery is the system of choice. Section 4 presents a summary of the preliminary design package. Major items included here, but not previously, are a fuel-treatment facility, preliminary design of a building, preliminary layouts of equipment, including a cooling tower on the roof of an existing building. Section 5 provides a financial analysis based on the design package. In comparison to Phase I, capital costs increased considerably due to the addition of a separate building, fuel treatment, and the use of a more-expensive No. 6-oil-burning engine. It is found, however, that the project continues to be financially viable. Specifically, a 9.4-year-payback period is projected on a total Clark investment of $1.5 million. Total cost, including DOE-financed feasibility studies and demonstration aspects, is projected at $2.2 million. The Clark ICES system is still a generally attractive project. From a national point of view it clearly demonstrates grid-connected cogeneration through the sale of 40% of Clark's output and a net fuel saving of 30%. From Clark's point of view it serves as a sound investment and a useful hedge against inflation and future changes in utility rate structure.